Defining barriers to food systems sustainability: A novel conceptual framework - Even, Brice; Thai, Hang Thi Minh; Pham Thi, Huong Mai; Bene, Christophe (Frontiers Media, 2024)
The transformation of food systems emerges as a critical challenge necessitating a deep, holistic comprehension of the complex and multifaceted barriers that hinder progress towards sustainability. The existing literature is not consistent in identifying these barriers. Building upon existing work, this paper introduces a comprehensive, integrated, and interdisciplinary framework to dissect the nature and origins of the barriers to food system sustainability. Our framework categorizes these impediments into five domains: political economy, socio-technical, socio-cultural, biophysical, and socio-economic barriers, and highlights their intricate interplay and interconnected nature. We pinpoint the foundational role of political economy barriers as the cornerstone of a “system of barriers” that create or perpetuate unsustainability. This framework not only advances academic knowledge by providing a structured basis for analysing sustainability barriers but also serves as a practical tool for policymakers, researchers, and practitioners, to foster transdisciplinarity and develop targeted interventions. We call for further empirical research, emphasizing the need for comparative analyses, longitudinal studies, and the exploration of feedback loops and non-linear dynamics between barriers, to inform effective and sustainable food system transformation strategies.